I’m human too: Person-centred counsellors’ lived experiences of therapist self-disclosure - Jolley, Helen Kathryn (European Journal for Qualitative Research in Psychotherapy, 2019)
Therapist self-disclosure (TSD) is an issue shrouded in debate, risk, and uncertainty. However, it can also serve as a useful therapeutic tool for those who decide to ‘take the plunge’. Given the paucity of research on person-centred counsellors’ perspectives of TSD, this study sought to explore two person-centred counsellors’ lived experiences of self-disclosing personal information to clients during therapy. Semi-structured interviews were conducted, which were recorded and transcribed. A hermeneutic phenomenological approach was adopted to allow an in-depth examination of the counsellors’ subjective, pre-reflective lived experiences. Four main themes emerged: ‘An internal battle’; ‘Levelling the playing field’; ‘Normalising experiences’; and ‘I’m human too’. Each theme is described in detail with reference to relevant phenomenological concepts. Within the analysis, the implicit power of TSD is revealed - particularly in relation to its potential to ‘level the playing field’, but also in terms of the position of power held by the practitioner. Potential implications for practitioners are touched upon within the discussion. Also explored within the discussion are the ways in which TSD may serve to facilitate a range of therapeutic goals - including strengthening the therapist-client relationship - which could have direct clinical implications for therapists; particularly, person-centred counsellors.